The Antimicrobial Effect of Cornus mas L. and Sorbus aucuparia L. Fruit Extracts against Resistant Uropathogens in Correlation with the Prevalence of Urinary Tract Infections in Companion Animals - Mara Aurori; Cristiana Ștefania Novac; George Cosmin Nadăș; Smaranda Crăciun; Nicodim Fiţ; Sanda Andrei (MDPI AG, 2024)
Urinary tract infections (UTIs) are a widespread condition in pets, with many antibiotics being prescribed, contributing to the rise in antimicrobial resistance, which is a worldwide threat. This study's main objective was to analyze the in vitro antimicrobial activity of Cornus mas and Sorbus aucuparia fruit hydro-ethanolic extracts towards bacteria identified in the urine of companion animals experiencing UTIs. Urine samples were collected from dogs and cats (n = 83; 47 negative, 36 positive); several bacterial strains were identified (n = 49) belonging to the Escherichia, Enterococcus, Staphylococcus, Proteus, Klebsiella, Enterobacter, Pseudomonas, Acinetobacter, Leclercia, and Kocuria genera. Bacterial susceptibility was tested using the disk diffusion method, with the majority being resistant to several beta-lactams, quinolones, trimethoprim/sulfamethoxazole, and nitrofurantoin. Subsequently, 13 resistant isolates were selected to evaluate the fruits extracts' antimicrobial potential using the agar well diffusion and broth microdilution methods. Cornus mas exhibited the greatest activity against Gram-negatives (primarily Pseudomonas luteola), while Sorbus aucuparia showed maximum effects towards Gram-positives (particularly Enterococcus faecalis). The MIC was 0.01 μg/μL for both extracts; the MBC was 0.08 μg/μL for Cornus mas and 0.05 μg/μL for Sorbus aucuparia. However, Cornus mas showed a stronger bactericidal effect. This is the first study to investigate these fruit extracts in UTI isolates of companion animals, and these extracts might be used as substitutes or adjuvants for antibiotics, thus contributing to a reduction in antimicrobial resistance.